2004
DOI: 10.2135/cropsci2004.1330
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Seedling Bermudagrass to Postemergence Herbicides

Abstract: The introduction of improved seeded cultivars of bermudagrass [Cynodon dactylon (L.) Pers.] has generated significant interest from the turfgrass industry. An important component of successfully establishing these new cultivars will be to develop effective weed control strategies for the critical establishment period. A field study and a greenhouse study were conducted to evaluate the tolerance of several seeded bermudagrasses to commonly used postemergence herbicides at different periods of establishment. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 14 publications
6
42
0
Order By: Relevance
“…For those herbicides that are used to control grassy weeds, quinclorac had good safety on seedling bermudagrass (Figs. 1 through 4), which is in agreement with earlier reports (6,8,11). When quinclorac was tank‐mixed with MSMA, herbicide injury was increased (Fig.…”
Section: Herbicide Injury On Seedling ‘Riviera’ Bermudagrasssupporting
confidence: 94%
See 4 more Smart Citations
“…For those herbicides that are used to control grassy weeds, quinclorac had good safety on seedling bermudagrass (Figs. 1 through 4), which is in agreement with earlier reports (6,8,11). When quinclorac was tank‐mixed with MSMA, herbicide injury was increased (Fig.…”
Section: Herbicide Injury On Seedling ‘Riviera’ Bermudagrasssupporting
confidence: 94%
“…4). Earlier trials at this location with metsulfuron revealed similar results on this and other seeded bermudagrass cultivars (6). Foramsulfuron and trifloxysulfuron were tested in a previous trial against four seeded bermudagrass cultivars, including ‘Riviera,’ and found to have good safety when applied at 4 to 7 weeks after emergence (8).…”
Section: Herbicide Injury On Seedling ‘Riviera’ Bermudagrasssupporting
confidence: 78%
See 3 more Smart Citations